Perceived Environmental Stressors and Pain Perception During Labor Among Primiparous and Multiparous Women - M Pirdel; L Pirdel (JRI, 2009)
Introduction: Pain experienced during labor is probably the most painful event in the lives of women. Environment itself influences a mother's experience of pain. Tension and stress resulting from pregnancy crisis and labor increase when the mother is hospitalized, which is concomitant with stressful situations and factors that affect pain perception during labor. The purpose of this study was to explore selected aspects of labor stress and specifically study the relationship between environmental factors and pain perception among parturient women. Materials and Methods: This descriptive-comparative study was carried out in Tabriz Alzahra Hospital during 2005-2006. In this study, 300 primiparous and 300 multiparous women who were candidates for vaginal delivery, were randomly selected and interviewed. The data were collected by a questionnaire and the intensity of pain was determined by Visual Analogue Scale (VAS).Results: Significant positive correlations were found between pain and tension from environmental factors in primiparous (r=0.16, p<0.01) and in multiparous (r=0.22, p<0.05) women. Furthermore, primiparous women believed that a crowded delivery room (70%) and restriction of movement and mobility (67%) contributed to their environmental stresses. Multiparas women believed that noise in the delivery ward (84%) and restrict of fluid intake (78%) increased their stresses. Conclusion: Performance of routine diagnostic tests in hospitalized pregnant woman, provision of invasive medical care during labor process and a noisy and crowded environment all influence the mother's experience and perception of pain. Therefore, the medical staffs seem to play a great role in alleviating labor pain by reducing stressors, especially the objective ones that are more stressful.
Keywords: Stress, Labor pain, Pain Perception, Primiparous, Multiparous, Environmental factors